Resistorless Cascadable Current-Mode Filter Using CCCFTAS - Witthaya Mekhum; Winai Jaikla (My University, 2013)
The realization of current-mode biquad filter using current controlled current follower transconductance amplifiers (CCCFTAs) and grounded capacitors is presented. The proposed filter can simultaneously provide three standard transfer functions (low pass, high pass and band pass filter). The tuning of quality factor can be done without affecting the pole frequency. Low input and high output impedances of the configurations enable the circuit to be cascaded without additional current buffers. The use of only grounded capacitors is ideal for integration. The circuit performances are depicted through PSpice simulations, they show good agreement to theoretical anticipation.
Keywords: Digital biquad filter; Current-feedback operational amplifier; Operational transconductance amplifier; Transconductance; All-pass filter; Current conveyor; Analog and Mixed-Signal Circuit Design